The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acsami.7b12946
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analyses of Phase Stability in Amorphous and Partially Crystallized Ge-Rich GeTe Films Prepared by Atomic Layer Deposition

Abstract: The local bonding structures of GeTe (x = 0.5, 0.6, and 0.7) films prepared through atomic layer deposition (ALD) with Ge(N(Si(CH))) and ((CH)Si)Te precursors were investigated using Ge K-edge X-ray absorption spectroscopy (XAS). The results of the X-ray absorption fine structure analyses show that for all of the compositions, the as-grown films were amorphous with a tetrahedral Ge coordination of a mixture of Ge-Te and Ge-Ge bonds but without any signature of Ge-GeTe decomposition. The compositional evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The structure of the Te­(SiMe 3 ) 2 precursor is identical to that in the previous works. ,, The established ALD process, shown in Figure b, consisted of Ge­(guan)­NMe 2 pulse/purge and co-injection of Te­(SiMe 3 ) 2 and NH 3 and purge. The reason for such a peculiar ALD sequence setup was as follows.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The structure of the Te­(SiMe 3 ) 2 precursor is identical to that in the previous works. ,, The established ALD process, shown in Figure b, consisted of Ge­(guan)­NMe 2 pulse/purge and co-injection of Te­(SiMe 3 ) 2 and NH 3 and purge. The reason for such a peculiar ALD sequence setup was as follows.…”
Section: Resultsmentioning
confidence: 70%
“…While this is not a sufficiently high performance for the storage-class memory application where a switching cycle of >∼10 8 –10 10 is required, it is still promising for the mass-storage device, such as Intel’s recent Optane for solid-state drive application. More importantly, this work elucidated that fundamental chemical research for the new precursor synthesis and extensive engineering works for optimizing the ALD process can pave the way for implementing the ALD GeTe films for actual device application, which has not been the case in the previous works. ,,,,, The GeTe ALD process described here has high potential utilities for building crystalline-as-deposited GST materials whose crystallization temperature is below 180 °C for further performance improvement as described in more detail in a separate paper …”
Section: Discussionmentioning
confidence: 88%
“…The FT was processed on k 2 -weighted ( k : electron momentum) EXAFS in a range of 2–10 Å –1 using a Hanning window. 41 The FT EXAFS magnitudes show the bonding distributions of Er ions in both samples. The overall FT spectra are very different from each other, suggesting that the local environment of Er in the x = 0.2 sample is fundamentally different from that of Er 2 O 3 .…”
Section: Resultsmentioning
confidence: 95%
“…The composition of the GeTe film was close to that of Ge 0.6 Te 0.4 , which was confirmed by X-ray fluorescence spectroscopy and TEM-EDS. It was revealed that the as-grown GeTe films were amorphous with a tetrahedral Ge coordination of a uniform mixture of (major) Ge–Te and (minor) Ge–Ge bonds, according to the X-ray absorption fine structure analysis [20].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, an atomic-layer-deposited GeTe-based PCRAM device was fabricated on TiN and W as BE, and the effect of electrode material on the crystallization of the GeTe phase-changing material was investigated. GeTe or Ge–Sb–Te phase-changing material, fabricated via atomic layer deposition (ALD), shows excellent step coverage even in a very-high-aspect-ratio (20:1) trench structure [17,18,19,20]. In addition, the conformal deposition will guarantee uniformity in electrical properties, including the crystallization process, because the void and adhesion issue can be avoided.…”
Section: Introductionmentioning
confidence: 99%